Komponen Pemasaran Teh Herbal Bukit Hexon pada PT. Karya Pak Oles Tokcer Denpasar Bali - LUMBANTORUAN, STEVI VIONA; WIDYANTARA, I WAYAN; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Marketing component of Herbal Tea Bukit Hexon at PT. Karya Pak Oles Tokcer Denpasar Bali Marketing is a combination of four variables that are the core of the company's marketing system, consisting of product, price, place/distribution channels, and promotions. This study is aimed at identifying the components of marketing carried out by PT. Karya Pak Oles Tokcer and the constraints faced in marketing their products. The research location was selected by purposive sampling. Types of data collected included primary and secondary data. Data were collected by observation, interview, and documentation study. Data were analyzed descriptively and qualitatively. Based onthe results of research known component of the marketing done by PT. By Pak Oles lessening of the products that the company provides one type of packing to look more attractive in the eyes of connsumers, this type of use the packing box. The selling price of tea sold is determined based on a calculation of raw material usage, labor, production, operating costs and other costs. Based on the place/distribution channels, herbal tea Bukit Hexon marketed through direct marketing distribution channel and indirectly. Promotional products are made through direct marketing activities (sales counter), sales promotion (rebates and bonuses) and advertising (flyers, newspaper and radio from the company it self). Constraints facing the company consists of internal and external constraints. Internal constraints in terms of the promotion are less effective. External constraints in terms of competitors’ similar products. Suggested the company should use the print media, better known by the public such as the Bali Post and electronic media such as ads on television so that are building relationships with the community and having a promotion more aggressively by opening a special stand tea sales as practiced by companies other tea products.